2018
DOI: 10.1088/1674-1137/42/3/034102
|View full text |Cite
|
Sign up to set email alerts
|

Pairing-energy coefficients of neutron-rich fragments in spallation reactions

Abstract: The ratio of pairing-energy coefficient to temperature (ap/T ) of neutron-rich fragments produced in spallation reactions has been investigated by adopting an isobaric yield ratio method deduced in the framework of a modified Fisher model. A series of spallation reactions, 0.5A and 1A GeV 208 Pb + p, 1A GeV 238 U + p, 0.5A GeV 136 Xe + d, 0.2A, 0.5A and 1A GeV 136 Xe + p, and 56 Fe + p with incident energy ranging from 0.3A to 1.5A GeV, has been analysed. An obvious odd-even staggering is shown in the fragment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…In particular, the study of thermodynamics is essential for compound nuclei, heavy ion collisions and induced fusions [1][2][3][4][5]. Studies have shown that the pairing correlation plays a very important role in these phenomena and other nuclear thermodynamic properties [6], such as the shape transition in hot nuclei [7,8], the phase diagram structure of liquid-gas phase transition [9,10], and the fragments produced in spallation reactions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the study of thermodynamics is essential for compound nuclei, heavy ion collisions and induced fusions [1][2][3][4][5]. Studies have shown that the pairing correlation plays a very important role in these phenomena and other nuclear thermodynamic properties [6], such as the shape transition in hot nuclei [7,8], the phase diagram structure of liquid-gas phase transition [9,10], and the fragments produced in spallation reactions [11].…”
Section: Introductionmentioning
confidence: 99%